The computer program Tailings-DEM™ modeling the strength properties of Musselwhite tailings matrices - Mahmood, Ali A; Elektorowicz, Maria (Journal of physics. Conference series, 2018)
Mine tailings are the waste materials from mining operations. They are traditionally stored in tailings ponds that have been the subject of several environmental catastrophes that resulted in the contamination of the environment and underground water resources. This paper presents the development of a numerical tool, called Tailings-DEM, for simulating the unconfined compressive strength of Musselwhite tailings, which are sandy materials. This tool is developed based on the Discrete Element Method and the programming language C++. It is shown here that Tailings-DEM™ can be utilized to model Musselwhite tailings matrices and sands with a particle size distribution close to Musselwhite tailings. Additionally, it can be used to model demolition waste, coal mine refuse and Chat.